"En-Face" Spectral-Domain Optical Coherence Tomography Findings in Multiple Evanescent White Dot Syndrome. (22nd April 2014) - De bats, Flore; Wolff, Benjamin; Vasseur, Vivien; Affortit, Aude; Kodjikian, Laurent; Sahel, José-Alain; Mauget-faÿsse, Martine
Abstract : Purpose . The recent use of "en-face" enhanced-depth imaging spectral-domain optical coherence tomography (EDI SD-OCT) helps distinguish the retinal layers involved in the physiopathology of multiple evanescent white dot syndrome (MEWDS). Methods . Four patients presenting with MEWDS underwent a comprehensive ocular examination including C-scan ("en-face") EDI SD-OCT at the initial visit and during follow-up. Results . C-scans combined with the other multimodal imaging enabled the visualization of retinal damage. Acute lesions appeared as diffuse and focal disruptions occurring in the ellipsoid and interdigitation zones. The match between autofluorescence imaging, indocyanine green angiography, and "en-face" OCT helped identify the acute microstructural damages in the outer retina further than the choroid. Follow-up using "en-face" EDI-OCT revealed progressive and complete recovery of the central outer retinal layers. Conclusion . "En-face" EDI SD-OCT identified the site of initial damage in MEWDS as the photoreceptors and the interdigitation layers rather than the choroid. Moreover, "en-face" OCT is helpful in the follow-up of these lesions by being able to show the recovery of the outer retinal layers.